Association between sarcopenia and oral functions in community‐dwelling older adults: A cross‐sectional study. Issue 1 (5th December 2022) - Kugimiya, Yoshihiro; Iwasaki, Masanori; Ohara, Yuki; Motokawa, Keiko; Edahiro, Ayako; Shirobe, Maki; Watanabe, Yutaka; Taniguchi, Yu; Seino, Satoshi; Abe, Takumi; Obuchi, Shuichi; Kawai, Hisashi; et al.
Abstract: Background: Few studies have examined the state of oral function in older adults with sarcopenia. We assessed the oral functions of community‐dwelling older adults with sarcopenia from multiple perspectives to clarify their potentially low oral function. Methods: A total of 1517 (86.2%; 990 women, 527 men; mean age 76.1 ± 7.6 years) participants were included in this study. Grip strength, gait speed and skeletal muscle mass index were assessed, and sarcopenia was evaluated according to the criteria of the Asian Working Group for Sarcopenia 2019. The degree of tongue coating, oral moisture, occlusal force, tongue–lip motor function, tongue pressure, masticatory function and swallowing function were assessed. The criteria for oral hypofunction (a disease that is a combination of multiple low oral functions) were used to assess oral function. Statistical analyses were performed using Kolmogorov–Smirnov test, unpaired t ‐test, Mann–Whitney U test, χ 2 test, and univariate and multivariable logistic regression analyses, with each oral function as the dependent variable and sarcopenia as one of the independent variables. The significance level was set at P < 0.05. Results: The prevalence rates of sarcopenia and severe sarcopenia were 14.2% and 3.8%, respectively. The prevalence of oral hypofunction was 39.9%. Compared with the robust group, the sarcopenia and severe sarcopenia groups tended to have a higher frequency of the following components (all P < 0.01): low occlusal force, low tongue–lip motor function, low tongue pressure, low masticatory function, low swallowing function and oral hypofunction. Univariate logistic regression analysis showed that sarcopenia was associated with low occlusal force, low tongue–lip motor function, low tongue pressure, low masticatory function, low swallowing function and oral hypofunction. The odds ratios and 95% confidence intervals of sarcopenia for each oral function were 2.62 [2.00, 3.43], 2.21 [1.69, 2.89], 3.66 [2.79, 4.81], 3.23 [2.46, 4.25], 1.66 [1.26, 2.20] and 3.59 [2.72, 4.72], respectively. Multivariable logistic regression analysis showed that sarcopenia was associated with low occlusal force (1.63 [1.10, 2.40]), low tongue pressure (2.28 [1.65, 3.15]), low masticatory function, (1.94 [1.27, 2.97]), low swallowing function (1.64 [1.17, 2.28]) and oral hypofunction (2.17 [1.52, 3.09]). Conclusions: This study demonstrated that multiple aspects of oral function were low among community‐dwelling older adults with sarcopenia. The potential decline in oral functions in older adults with sarcopenia may have been overlooked until now. This study indicates the need for dental perspectives in intervening with older adults with sarcopenia and the need to encourage them to see dental professionals.